2006
DOI: 10.1634/stemcells.2006-0074
|View full text |Cite
|
Sign up to set email alerts
|

Iron Particles for Noninvasive Monitoring of Bone Marrow Stromal Cell Engraftment into, and Isolation of Viable Engrafted Donor Cells from, the Heart

Abstract: Stem cells offer a promising approach to the treatment of myocardial infarction and prevention of heart failure. We have used iron labeling of bone marrow stromal cells (BMSCs) to noninvasively track cell location in the infarcted rat heart over 16 weeks using cine-magnetic resonance imaging (cine-MRI) and to isolate the BMSCs from the grafted hearts using the magnetic properties of the donor cells. BMSCs were isolated from rat bone marrow, characterized by flow cytometry, transduced with lentiviral vectors ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 40 publications
2
126
1
1
Order By: Relevance
“…We, and others, have shown that the contrast generated by ironlabeled cells increases with the amount of iron/voxel but that this is only linear at low iron loadings; the change in contrast reaches a saturation plateau at higher iron loadings. 6,7 When quantifying the presence of iron-labeled stem cells over time, most studies measure the "signal void volume" 8,9 or the "number of black pixels", 10,11 and present the change relative to the first imaging time point.…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have shown that the contrast generated by ironlabeled cells increases with the amount of iron/voxel but that this is only linear at low iron loadings; the change in contrast reaches a saturation plateau at higher iron loadings. 6,7 When quantifying the presence of iron-labeled stem cells over time, most studies measure the "signal void volume" 8,9 or the "number of black pixels", 10,11 and present the change relative to the first imaging time point.…”
Section: Introductionmentioning
confidence: 99%
“…5 Over the past 10 years, many preclinical studies and clinical trials have used SPIO and cardiac magnetic resonance (CMR) imaging to deliver, track, or determine the efficacy of stem cell therapy in the heart. [6][7][8][9][10][11][12][13][14] The detected signal is used to estimate the number of cells. Even recently, SPIO was still used to label and assess the long-term (2 months) survival of human-induced pluripotent stem cellderived cardiomyocytes in infarcted myocardia of mini-pigs.…”
mentioning
confidence: 99%
“…Adequate methods for monitoring these aspects have recently been described; it was shown recently that iron-oxide labelled cells can be visualized by MRI thereby allowing migration and engraftment to be directly monitored in the heart. 65 In addition, hybrid imaging systems (two or more imaging modalities) are emerging, [66][67][68][69] paving the way for simultaneously monitoring the heart at a global, regional and molecular level under the conditions of interest. Based on these trends, the future of imaging seems to be in multi-scale approaches; from global to regional to imaging at the molecular level, in a multimodality based manner.…”
Section: The Use Of Imaging Technologiesmentioning
confidence: 99%